BASES FOR THE FORMATION OF THE LEXICIAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS FOR FUTURE PROFESSIONAL ACTIVITY IN THE DIALECT ENVIRONMENT - Nakonechna, Larysa (Mountain School of Ukrainian Carpaty, 2019)
The article deals with the formation of the lexical competence of future elementary school teachers in the program, which prepares for the work activity in the conditions of the dialectal environment. The author analyzed several definitions of the «lexical competence» concept, the scientific’s’ views for the formation of lexical competence of primary pupils and students which study «Primary Education» specialty. Also, the author worked out a number of pedagogical and methodological works, defined the concept of «lexical competence» and «lexical competence of the primary school teacher», defined the directions of preparation for work in the dialectal environment those students who study «Primary education» specialty the author argued the need of the universities disciplines which form the readiness of future language teachers for the work in the dialectical environment. The purpose of the article is to analyze the formation of lexical competence of the «Primary education» specialty students while preparation for the work in the dialectal environment. The purpose is due to the lack of the Programs, which guide how teachers should work with dialect speaking pupils. The author analyzed the current Programs of the Ministry of Education and Science of Ukraine for the primary schools, and found that there are no any recommendations to the teacher on how to work in local dialects there. Similarly, there are no exercises for studying the literary language through the comparison with dialecticisms in Ukrainian language textbooks. On the other hand, we should not ignore the active functioning of the dialects and the fact that primary school teachers work with pupils who are dialect speakers. The article author described the results of the researching, which proves the effectiveness of studying the literary Ukrainian language through comparison with the local dialects that children speak. The urgency of the topic is connected with the fact that it is necessary to improve the system of training of future elementary school students and the methodology of formation of primary pupils’ language personalities. So, formation of lexical competence has the leading place in the language training for primary school pupils.